Aneurysms in childhood: literature review and cases description - Daniel Gregório Gonsalves; Manuela Guedes Pereira; Pedro Henrique Simm Pires de Aguiar; Fernanda Lopes Rocha Cobucci; Marcelo Ughini Crusius; Roberto Alexandre Dezena; Paulo Henrique Pires de Aguiar (Brazilian Society for Pediatric Neurosurgery, 2022)
Introduction: In the aneurysm disease, children aneurysms do not represent a majority of the diagnosis. Associated conditions should be monitored, including aortic coarctation, polycystic kidney disease, fibromuscular dysplasia, tuberous sclerosis, Ehlers-Danlos syndrome, and Marfan syndrome. They can present as congenital, infectious, or traumatic. Case report: We describe a series of five cases of aneurysms in patients ranging from 15 to 17 years of age whose aneurysms were found on examination. In most cases, patients were asymptomatic and did not have predisposing syndromes. Surgery was the treatment of choice in all cases. No patient had a recurrence in the following years of radiographic follow-up. Methodology: This is a literature review and case series analysis with a narrative-descriptive approach. The database for the search was PubMed®, which were used to search for articles with the subject descriptors brain, aneurysms, pediatric and child. Between the descriptors, the boolean operator and was used.  Discussion: Aneurysms can be classified by their size and morphology, as well as having a predilection for anterior circulation. The most common symptom observed in our pediatric series of 5 patients was migraine or chronic headache (60%), followed by asymptomatic patients  (40%). Three of five patients (60%) in this study were previously hypertensive without other comorbidity, while 40% of the cases were totally healthy. Conclusion: Pediatric intracranial aneurysms are relatively rare diseases, corresponding to 1.6 to 7% of intracranial aneurysms across all age groups. They require accurate and detailed diagnosis, which need to be assessed and managed in a multidisciplinary team.